Earth system impacts of the European arrival and Great Dying in the Americas after 1492. (1st March 2019) - Koch, Alexander; Brierley, Chris; Maslin, Mark M.; Lewis, Simon L.
Abstract: Human impacts prior to the Industrial Revolution are not well constrained. We investigate whether the decline in global atmospheric CO2 concentration by 7–10 ppm in the late 1500s and early 1600s which globally lowered surface air temperatures by 0.15 ∘ C, were generated by natural forcing or were a result of the large-scale depopulation of the Americas after European arrival, subsequent land use change and secondary succession. We quantitatively review the evidence for (i) the pre-Columbian population size, (ii) their per capita land use, (iii) the post-1492 population loss, (iv) the resulting carbon uptake of the abandoned anthropogenic landscapes, and then compare these to potential natural drivers of global carbon declines of 7–10 ppm. From 119 published regional population estimates we calculate a pre-1492 CE population of 60.5 million (interquartile range, IQR 44.8–78.2 million), utilizing 1.04 ha land per capita (IQR 0.98–1.11). European epidemics removed 90% (IQR 87–92%) of the indigenous population over the next century. This resulted in secondary succession of 55.8 Mha (IQR 39.0–78.4 Mha) of abandoned land, sequestering 7.4 Pg C (IQR 4.9–10.8 Pg C), equivalent to a decline in atmospheric CO2 of 3.5 ppm (IQR 2.3–5.1 ppm CO2 ). Accounting for carbon cycle feedbacks plus LUC outside the Americas gives a total 5 ppm CO2 additional uptake into the land surface in the 1500s compared to the 1400s, 47–67% of the atmospheric CO2 decline. Furthermore, we show that the global carbon budget of the 1500s cannot be balanced until large-scale vegetation regeneration in the Americas is included. The Great Dying of the Indigenous Peoples of the Americas resulted in a human-driven global impact on the Earth System in the two centuries prior to the Industrial Revolution. Highlights: Combines multiple methods estimating pre-Columbian population numbers. Estimates European arrival in 1492 lead to 56 million deaths by 1600. Large population reduction led to reforestation of 55.8 Mha and 7.4 Pg C uptake. 1610 atmospheric CO2 drop partly caused by indigenous depopulation of the Americas. Humans contributed to Earth System changes before the Industrial Revolution.